Long-term prognosis in patients with thymoma combined with myasthenia gravis: a propensity score-matching analysis - Zhao, Kai; Liu, Yiming; Jing, Miao; Cai, Wenhan; Jin, Jiamei; Zhu, Zirui; Shen, Leilei; Wen, Jiaxin; Xue, Zhiqiang (Frontiers in Medicine, 2024)
We aimed to assess the impact of myasthenia gravis (MG) on the long-term prognosis in patients with thymoma after surgery and identify related prognostic factors or predictors.This retrospective observational study included 509 patients with thymoma (thymoma combined with MG [MG group] and thymoma alone [non-MG group]). Propensity score matching was performed to obtain comparable subsets of 96 patients in each group. A comparative analysis was conducted on various parameters.Results: Before matching, the 10-year survival and recurrence-free survival rates in both groups were 93.8% and 98.4%, and 85.9% and 93.4%, respectively, with no statistically significant difference observed in the survival curves between the groups (P>0.05). After propensity score matching, 96 matched pairs of patients from both groups were created. The 10-year survival and recurrence-free survival rates in these matched pairs were 96.9% and 97.7%, and 86.9% and 91.1%, respectively, with no statistical significance in the survival curves between the groups (P>0.05). Univariate analysis of patients with thymoma postoperatively revealed that the World Health Organization histopathological classification, Masaoka-Koga stage, Tumor Node Metastasis stage, resection status, and postoperative adjuvant therapy were potentially associated with tumor recurrence after thymoma surgery. Multivariate analysis demonstrated that the Masaoka-Koga stage and postoperative adjuvant therapy independently predicted the risk of recurrence in patients with thymoma after surgery.There was no difference in prognosis in patients with thymoma with or without MG.The Masaoka-Koga stage has emerged as an independent prognostic factor affecting recurrence-free survival in patients with thymoma, while postoperative adjuvant therapy represents a poor prognostic factor.